ANALISIS STRUKTUR MODAL, FUNDAMENTAL MAKRO, KARAKTERISTIK PERUSAHAAN, DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FOOD & BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2021-2024 - Indah Naila Prisca; Hwihanus Hwihanus (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to examine and analyze the impact of capital structure, macroeconomic conditions, firm characteristics, and liquidity on financial performance, with profitability as an intervening variable, among food and beverage companies listed on the Indonesia Stock Exchange for the period 2021 to 2024. This research employs an explanatory quantitative method using the SEM-PLS approach supported by SmartPLS software. The sample consists of eight companies selected through purposive sampling based on the criteria of having complete financial reports and not being delisted during the research period. The findings indicate a significant positive influence of capital structure and firm characteristics on profitability, while macroeconomic conditions and liquidity show no significant effect. Furthermore, the results reveal that firm characteristics and profitability significantly affect financial performance, whereas capital structure, macroeconomic conditions, and liquidity do not exhibit a direct impact. Profitability also serves as a mediating variable that links the effects of capital structure and firm characteristics to financial performance. These results suggest that internal company factors play a more dominant role than external factors in determining profitability and financial performance in the food and beverage sector.